Market forces and world development - Prendergast, R (Macmillan Press, 1994)
Eleven papers, originally presented at the Development Studies Association's Annual Conference held at the University of Swansea in September 1991, provide diverse explanations of why increasing interdependence in the global economy is not leading to a greater degree of convergence in terms of welfare and development and why competitive forces do not necessarily lead to a single optimal equilibrium. Nigel Harris examines nationalism and development. Dharam Ghai explores structural adjustment, global integration, and social democracy. Renee Prendergast discusses increasing returns and economic development. Peter Smith assesses market forces and development. Kunibert Raffer focuses on disadvantaging comparative advantages. Alexandre Rands Barros addresses development and standard of living. John Toye explores the appraisal and evaluation of structural adjustment lending. Frances Stewart examines education and adjustment. Des Gasper discusses development ethics. Edward Clay focuses on the decline of food aid. H. W. Singer presents two views of food aid. Prendergast is at Queen's University, Belfast. Stewart is at the University of Oxford. Index.